Laparoscopic inguinal hernia repairs: comparison between TAPP and TEP at a tertiary center of Nepal - Gurung, Komal B.; Banepali, Niroj; Sthapit, Rakesh R.; Adhikari, Baikuntha (International Surgery Journal, 2018)
Background: Laparoscopic inguinal hernia repair has been proven to be a safe and effective procedure for groin hernias. In recent years, many of the tertiary centers in Nepal have started performing laparoscopic hernia repair. With the availability of resources and the facilities, the laparoscopic repairs for inguinal hernias are going to be more accessible in near future in Nepal. The aim of this study was to compare the intraoperative events and postoperative complications of transabdominal preperitoneal (TAPP) and totally extraperitoneal (TEP) techniques of laparoscopic inguinal hernia repairs. Methods: Out of 56 patients, 30 underwent TAPP and 26 TEP repairs for primary unilateral inguinal hernias and were prospectively analyzed. Patient demographics, past medical and surgical history, intraoperative, and postoperative events were recorded. Patients were followed-up for two years. Results: Demographic parameters were comparable in both the groups. The difference in mean operating time was statistically significant (longer in the TAPP group). Intraoperative events such as port-site bleeding and peritoneal tear were comparable in both groups. The immediate postoperative complications like skin ecchymosis, cord hematoma, and scrotal edema were comparable in both repairs. Immediate postoperative pain was significantly lesser in TEP repair whereas the hospital stays and time to return to the normal physical activity were comparable in both groups. Conclusions: Both TAPP and TEP laparoscopic techniques are safe and effective for inguinal hernia repair. However, there are few advantages of TEP repair such as shorter duration of surgery and less postoperative pain.